Frequency of Hepatic Metastatic Disease in Patients with Stage IV Breast Cancer Is Similar for Steatotic and Non-Steatotic Livers - Adeel Haq; Tyler J Fraum; Yu Tao; Farrokh Dehdashti; Maverick LeBlanc; Mark J Hoegger; Jingqin Luo; Katherine Weilbaecher; Lindsay L Peterson (Breast Cancer: Basic and Clinical Research, 2023)
Background: Breast cancer is the most common non-cutaneous malignancy and the second leading cause of cancer mortality in the United States. Breast cancer is a heterogeneous disease; diagnosis at an early stage renders it potentially curable, whereas advanced metastatic disease carries a worse prognosis. Objectives: To investigate whether hepatic steatosis (HS) is associated with liver metastases in patients with newly diagnosed stage IV female breast cancer patients (either de novo metastatic breast cancer or recurrent metastatic breast cancer) using non-contrast computed tomography (CT) as a marker of HS. Design: Retrospective analysis. Methods: We retrospectively identified 168 patients with stage IV breast cancer with suitable imaging from a prospectively maintained oncologic database. Three radiologists manually defined hepatic regions of interest on non-contrast CT images, and attenuation data were extracted. HS was defined as a mean attenuation <48 Hounsfield units. The frequency of hepatic metastatic disease was calculated for patient with and without HS. Relationships between HS and various patient (age, body mass index, race) and tumor (hormone receptor status, HER2 status, tumor grade) characteristics were also analyzed. Results: There were 4 patients with liver metastasis in the HS group (41 patients) versus 20 patients with liver metastases in the non-HS group (127 patients). The difference in frequencies of liver metastases among patients with (9.8%) versus without (15.7%) hepatic steatosis (odds ratio = 1.72 [0.53-7.39]) was not statistically significant ( P  = .45). Body mass index was significantly higher ( P  = .01) among patients with hepatic steatosis (32.2 ± 7.3 vs 28.8 ± 7.1 kg/m 2 ). Otherwise, there were no significant differences between patients with versus without HS with respect to regarding age, race, hormone receptor status, HER2 status, or tumor grade. Conclusion: The frequency of hepatic metastatic disease in patients with stage IV breast cancer is similar for steatotic and non-steatotic livers.